ISLAMIZATION OF KNOWLEDGE - Fakhruddin Azmi, Mely Nadia (Yayasan Pendidikan Islam dan Multikultural, 2022)
Abstract The purpose of this discussion is to add insight and understanding about the Islamization of science, which means Islamizing or purifying Western product science, which has been developed and used as a reference in the discourse of creating an Islamic education system to obtain science with an